The Light Ages: Medieval Architecture and the Not-So-Dark Ages - Koser, Jessica Ann (My University, 2016)
The term “Dark Age” is frequently used when referring to the Medieval period. While many people use this label without realizing how it originated, people today still continue its usage. This paper will locate and gain an understanding of the origin and concept behind the utilization of the words “dark age” as well as the negative connotations associated with the phrase. Essentially, why did individuals from the Renaissance and until the recent past see the Dark Ages as dark? What were they seeing that was perceived as darkness? Additionally, the following paper will look at three architectural examples from the Medieval period, spanning the Carolingian, Romanesque and Gothic styles. The shining examples of these styles are the Palatine Chapel, Durham Cathedral and the Abbey Church of St. Denis, respectively. Also explored are the architectural elements and construction of these buildings to illustrate the complexity, level of talent, and intellect that was involved with producing these structures. By examining exemplary buildings such as these, one can come to the conclusion that the Medieval period was not a “dark age” but in fact a time of enlightened and talented artistic and architectural production and output that arguably shouldn’t have had any aspect of darkness attached to it.
Keywords: Architecture, Medieval; Middle Ages; Europe -- History -- 476-1492